Advances in PLC-based canal automation - Burt, Charles M., author; Piao, Xianshu, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2002)
A short history of canal automation is given. PLC-based canal automation is relatively new. Advances in PLC-based canal automation are listed. Also listed are some of the remaining challenges. Recent advances have been made in understanding unsteady flow simulation procedures, the form of the control algorithms used, the tuning procedures for these control algorithms, and the field programming of the algorithms into PLCs. The experiences of the Cal Poly Irrigation Training and Research Center (ITRC) in automating a variety of canals with upstream and downstream control are given.
USCID/EWRI conference
PLC-based canal automation
Not digitized by CSUL Digital Services.
Presented at the 2002 USCID/EWRI conference, Energy, climate, environment and water - issues and opportunities for irrigation and drainage on July 9-12 in San Luis Obispo, California.